Síndrome respiratória aguda grave em pessoas hospitalizadas por COVID-19 - Felix, Paulo Thomaz Oliveira (2022)
In 2019, China informed the World Health Organization - WHO, World Health Organization - WHO, World Health Organization - WHO, about an outbreak of a new disease with characteristics of pneumonia, being called covid-19 for the occurrence by SARS- CoV-2. While the virus can cause mild respiratory illness, it can cause Severe Respiratory Syndrome (SARS). Faced with the pandemic, an important relationship has been observed with social health factors and the results between the effects of covid-19. It aims to describe a prevalence of Severe Acute Respiratory Syndrome in people hospitalized for covid-19 in Sergipe. Retrospective cohort study. For the exploratory stage, the method of collecting secondary data was used. The database used was the SIVEP-gripe, for the availability of these data, the TCLE was waived by the Ethics and Research Committee Involving Human Beings of the Federal University of Sergipe (UFS). All positive cases of covid-19 that progressed to SARS will be included in this study. The March 2021 data collection took place through the cases in the March 2020 period. The data were organized in a Microsoft Excel platform and exported to the IMS SPSS. A completeness assessment of the independent variables was performed, adopting a significance level of 5%. 12 Absolute and relative frequencies were verified using Pearson's chi-square test. Poisson regression with robust variance and prevalence calculation were used to analyze possible associations of variables with outcomes, with a confidence interval of 95%. A multivariate analysis was used to verify possible confounding factors. For all exposures and outcomes, sample power was calculated. With the results, it was possible to observe that the majority of cases were male (57.5%), over 60 years old (57.4%), brown (73%), among those who had education information (44 .4%), 79.4% had completed elementary school, most were from urban areas (65.6%), 74% had some comorbidity, the most prevalent being Chronic Cardiovascular Disease (50.3%) and Diabetes Mellitus (36.9%). Among those with recorded information, 34.4% were admitted to the ICU and 21.4% died. Females were 25% more likely to be admitted to the ICU (RR: 1.25; 95%CI: 1.07-1.47). Patients aged over 60 years have a 342% higher risk (RR: 4.42; 95%CI: 1.28-15.27) of death. For evolution, prioritizing what increases the risk of death, the age group over 60 years old (RR: 1.43; 95% CI: 1.26-1.62), race/yellow color (RR: RR: 1.40; 95%CI: 1.21-1.61) or brown (RR: 1.19; 95%CI: 1.03-1.39). The study presented a large number of ignored cases, representing an underreporting. This study makes it possible to determine the most vulnerable audiences, making it possible to use this data to support and direct actions more effectively. Promoting the planning of actions aimed at surveillance, education and increasing care coverage, especially in places with the highest prevalence.